Improvisation Efforts in Islamic Educational Institutions: To Achieve Global Competitiveness - Ratu Suntiah; Mursidin; Ahmad Nanda Maulana; Sahrul Fadhil; Fahren Sepujan Nasution (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The world of education is now competing globally due to rapid advances in technology and information. Education serves as a benchmark for a country's progress because it shapes a generation with the ability to improve their skills and produce new information. Furthermore, educational institutions must improvise with changing times, and educational institutions must have a curriculum that is appropriate for global competition. Therefore, the purpose of this paper is for Islamic educational institutions to increase their competitiveness by improvising and refining a more relevant curriculum that can produce more adaptive Islamic educational values, thus creating students and a generation that is creative, innovative, religious, and moral, thus able to have global competitiveness.